A chimeric vaccine targeting Pseudomonas aeruginosa virulence factors protects mice against lethal infection. (May 2023) - Korpi, Fatemeh; Irajian, Gholamreza; Forouhi, Fatemeh; Mohammadian, Taher
Abstract: Pseudomonas aeruginosa is an important and hazardous nosocomial pathogen in respiratory tract infections and rapidly achieves antibiotic resistance, so it is necessary to develop an effective vaccine to combat the infection . The Type III secretion system (T3SS) protein P. aeruginosa V-antigen (PcrV), outer membrane protein F (OprF), and two kinds of flagellins (FlaA and FlaB) all play important roles in the pathogenesis of P. aeruginosa lung infection and its spread into deeper tissues. In a mouse acute pneumonia model, the protective effects of a chimer vaccine including PcrV, FlaA, FlaB, and OprF (PABF) protein were investigated . PABF immunization prompted robust opsonophagocytic titer of IgG antibodies and decreased bacterial burden, and improved survival afterward intranasal challenge with ten times 50% lethal doses (LD50) of P. aeruginosa strains, indicating its broad-spectrum immunity. Moreover, these findings showed a promise chimeric vaccine candidate to treat and control P. aeruginosa infections. Highlights: Complete protection of PcrV, FlaA, FlaB, and OprF (PABF) protein -immunized mice infected by P. aeruginosa strains. PABF prompts greater opsonophagocytic titer of IgG antibodies as compared to monovalent vaccines. PABF elicits effective immune responses to PcrV, OprF, FlaA and FlaB components; with no cross-reactive interference. PABF vaccine affords broad-spectrum protection against P. aeruginosa infections.